SGLSA: Sphygmus gated laser speckle angiography for microcirculation hemodynamics imaging. (January 2023) - Feng, Ximeng; Geng, Mufeng; Meng, Xiangxi; Zou, Da; Jin, Zi; Liu, Gangjun; Zhou, Chuanqing; Ren, Qiushi; Lu, Yanye
Abstract: Hemodynamics imaging of the retinal microcirculation has been demonstrated to be potential access to evaluating ophthalmic diseases, cardio-cerebrovascular diseases, and metabolic diseases. However, existing structural and functional imaging techniques are insufficient in spatial or temporal resolution. The sphygmus gated laser speckle angiography (SGLSA) is proposed for structural and functional imaging with high spatiotemporal resolution. Compared with classic LSCI algorithms, SGLSA presents a much clearer perfusion image and higher signal-to-noise ratio pulsatility. The SGLSA algorithm also shows better performance on patients than traditional LSCI methods. The high spatiotemporal resolution provided by the SGLSA algorithm greatly enhances the ability of retinal microcirculation analysis, which makes up for the deficiency of the LSCI technology, and attaches great significance to retinal hemodynamic imaging, biomarker research, and clinical diagnosis.